Effect of SWCNT dispersion on epoxy nanocomposite properties - Uzunpinar, Cihan (2012)
In nanocomposites containing single wall carbon nanotubes (SWCNTs), the final properties strongly depend on the dispersion quality of these fillers. Various methods have been used to improve the dispersion of nanofillers; however, one of the most effective ways is to functionalize carbon nanotubes (CNTs) with covalent and noncovalent functional groups. In this work, the dispersion of SWCNTs in an epoxy system was studied by using surfactants, acid (COOH), and ester groups (PGE)-modified CNTs. Rheological and scanning electron microscopy analysis showed that functionalization of CNTs helped in improving the dispersion of fillers in the epoxy matrix. Systems with surfactant modified SWCNTs (1 wt%) exhibited the highest storage modulus at low frequencies after 5-min sonication. This behavior is associated to a stronger network of fillers as a result of a good dispersion. However, longer sonication times lowered the storage modulus, corresponding to a degradation of the tubes. The effect of the dispersion quality on mechanical properties was also studied using a three-point bending set-up.